Religious Coping Strategies Among Divorced Single Mothers in Garut: Managing Stigma and Patriarchal Challenges - Annisa Qurrotul Ayuni; Purnairawan, Riski Eka (Sahabat Akademia Group, 2025)
This study examines how divorced single mothers in Garut, West Java, navigate social, cultural, and economic pressures in a society deeply rooted in patriarchal norms. It explores how religious coping strategies assist them in managing emotions, combating social stigma, and addressing gender injustice. This research employs a descriptive qualitative approach with a multiperspective framework to explore the experiences of four informants selected using purposive and snowball sampling techniques. Data were collected through in-depth interviews and thematically analyzed to identify key patterns in religious coping strategies. The study is grounded in Kenneth Pargament’s religious coping theory and Mary Wollstonecraft’s feminist theory, which provide a robust theoretical foundation. The findings reveal that religious coping strategies help single mothers cope with social and economic pressures through three main approaches. First, self-directing strategies strengthen independence and problem-solving skills. Second, deferring strategies provide emotional peace by entrusting outcomes to God. Third, collaborative coping enhances spiritual connections through prayer and dhikr. Furthermore, the reinterpretation of religious teachings plays a crucial role in challenging patriarchal norms, promoting dignity, resilience, and self-identity. These strategies not only support psychological well-being but also function as tools for empowerment and gender justice. However, this study is limited by its small sample size and localized scope, which may affect the generalizability of the findings.